Nitrogen Removal Efficiency for Pharmaceutical Wastewater with a Single-Stage Anaerobic Ammonium Oxidation Process - Lushen Zuo (International Journal of Environmental Research and Public Health, 2020)
A single-stage anaerobic ammonium oxidation (ANAMMOX) process with an integrated biofilm–activated sludge system was carried out in a laboratory-scale flow-through reactor (volume = 57.6 L) to treat pharmaceutical wastewater containing chlortetracycline. Partial nitrification was successfully achieved after 48 days of treatment with a nitrite accumulation of 70%. The activity of ammonia oxidizing bacteria (AOB) decreased when the chemical oxygen demand (COD) concentration of the influent was 3000 mg/L. When switching to the single-stage ANAMMOX operation, (T = 32–34 °C, DO = 0.4–0.8 mg/L, pH = 8.0–8.5), the total nitrogen (TN) removal loading rate and efficiency were 1.0 kg/m3/d and 75.2%, respectively, when the ammonium concentration of the influent was 287 ± 146 mg/L for 73 days. The findings of this study imply that single-stage ANAMMOX can achieve high nitrogen removal rates and effectively treat pharmaceutical wastewater with high concentrations of COD (1000 mg/L) and ammonium.